Screening for tuberculosis in neuro-ophthalmology. (1st November 2016) - Little, Leanne M.; Graviss, Edward A.; Foroozan, Rod; Lee, Andrew G.
ABSTRACT: Introduction : Timely detection of Mycobacterium tuberculosis ( Mtb ) remain critical in the effective management of patients with suspected tuberculosis (TB) disease. While recommendations for determination of latent TB or TB exposure in industrialized countries support the use of interferon-gamma release assays (IGRA), including the QuantiFERON Gold In-Tube (QFT-GIT) and T-SPOT. TB tests, disagreement exists within neuro-ophthalmologic practice on screening protocols for TB which affects ocular function. Areas covered : The authors have reviewed the current literature discussing the manifestation of tuberculosis in neuro-ophthalmic disease. Our literature search expands on current recommendations for TB screening in neuro-ophthalmology, including a comparison of the currently available tests for screening: the TST, QFT-GIT, and T-SPOT. TB tests. We review the literature on regional TB prevalence as it applies to clinical decision making for screening, as well as medical and social factors which may create a high-risk individual for neuro-ophthalmic tuberculosis. Expert c ommentary : The authors recommend that protocols for screening for neuro-ophthalmic tuberculosis involve directing recently developed IGRAs towards patients considered at high risk as determined by patient history, including medical and social risk factors, as well as epidemiologic data for TB prevalence in the region under consideration.